2021
DOI: 10.1101/2021.01.26.428315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imagined speech can be decoded from low- and cross-frequency features in perceptual space

Abstract: SummaryReconstructing intended speech from neural activity using brain-computer interfaces (BCIs) holds great promises for people with severe speech production deficits. While decoding overt speech has progressed, decoding imagined speech have met limited success, mainly because the associated neural signals are weak and variable hence difficult to decode by learning algorithms. Using three electrocorticography datasets totalizing 1444 electrodes from 13 patients who performed overt and imagined speech product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Our findings suggests that motor-auditory interaction is essential in hierarchical meter imagery, which may apply to meaningful nested structure of imagined speech as well (Tian and Poeppel, 2012;Proix et al, 2021). We analyzed connectivity at the beat rate, assuming that the beat rate is a reasonable proxy for the importance of motor to auditory flow, since it turned out that we did not have sufficient data to robustly fit an MVAR model capable of capturing causal flow at the meter frequencies.…”
Section: Neural Substrates Of Meter Imaginationmentioning
confidence: 99%
“…Our findings suggests that motor-auditory interaction is essential in hierarchical meter imagery, which may apply to meaningful nested structure of imagined speech as well (Tian and Poeppel, 2012;Proix et al, 2021). We analyzed connectivity at the beat rate, assuming that the beat rate is a reasonable proxy for the importance of motor to auditory flow, since it turned out that we did not have sufficient data to robustly fit an MVAR model capable of capturing causal flow at the meter frequencies.…”
Section: Neural Substrates Of Meter Imaginationmentioning
confidence: 99%
“…Here we found that low-gamma activity was the only feature that specifically predicted language expression in TD children, a logical finding as language expression is tightly related to the transformation of phonetic into articulatory features at the same timescale [87][88][89][90][91].…”
Section: Low-gamma Power Predicts Language Expression In Td But Not Children With Asdmentioning
confidence: 50%
“…Performance on the Speech-related Behavior Recognition task, while comparatively exhibiting the weakest performance, can also be considered the most challenging of the three classification tasks. The neural circuits for perceiving speech, and producing overt, mouthed, and imagined speech, are highly intertwined [43], [46], [47]. Nevertheless, it is encouraging that the context representations of the model appear to encode some neural correlates of these behaviors.…”
Section: Discussionmentioning
confidence: 99%